Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Bagi Hasil dan Tingkat Inflasi terhadap Belanja Modal di Provinsi Bengkulu Tahun 2018-2022 - Putri Darunnisa, Lala; Herawansyah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to determine how the impact of capital expenditure in Bengkulu Province from 2018 to 2022 is related to local original income (PAD), general allocation funds (DAU), profit-sharing funds (DBH), and inflation. The study population consisted of local original income, general allocation funds, profit-sharing funds, inflation rates, and capital expenditures. Ten cities and regencies in Bengkulu Province. This study uses secondary data on the implementation of the 2018–2022 Bengkulu Provincial APBD budget obtained from the Directorate General of Financial Balance. WarpPLS software version 7.0 will be used as a data analysis tool to review research data. The conclusion of this study shows that although the general allocation fund does not have a significant effect and the inflation rate has a significant negative influence on capital expenditure, local original income, and profit-sharing funds have a significant positive influence.